2011
DOI: 10.1002/qj.760
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of convection over the Black Forest mountains during COPS IOP15a

Abstract: Doppler-On-Wheels radar observations made during the Convective and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…: 140 m). The system operated between 25 May and 30 August 2007 and collected more than 500 hours of measurements, distributed over 58 measurement days (examples of measurements of BASIL from this field deployment are given in Behrendt et al, 2011;Chaboureau et al, 2011;Bennett et al, 2011;Corsmeier et al, 2011;Kiemle et al 2011; The major feature of BASIL is its capability to perform high-resolution measurements of atmospheric temperature and water vapour, both in daytime and night-time, based on the application of the rotational and vibrational Raman lidar techniques in the ultraviolet (UV) Di Girolamo et al, 2006, 2009aBhawar et al, 2011). Besides temperature and water vapour, BASIL measures particle backscatter at 355, 532 and 1064 nm, particle extinction coefficient at 355 and 532 nm and particle linear depolarization at 355 and 532 nm (Maestri et al, 2010;Griaznov et al, 2007;Di Girolamo et al, 1996, 2009b.…”
Section: Lidar and Radar Systemsmentioning
confidence: 99%
“…: 140 m). The system operated between 25 May and 30 August 2007 and collected more than 500 hours of measurements, distributed over 58 measurement days (examples of measurements of BASIL from this field deployment are given in Behrendt et al, 2011;Chaboureau et al, 2011;Bennett et al, 2011;Corsmeier et al, 2011;Kiemle et al 2011; The major feature of BASIL is its capability to perform high-resolution measurements of atmospheric temperature and water vapour, both in daytime and night-time, based on the application of the rotational and vibrational Raman lidar techniques in the ultraviolet (UV) Di Girolamo et al, 2006, 2009aBhawar et al, 2011). Besides temperature and water vapour, BASIL measures particle backscatter at 355, 532 and 1064 nm, particle extinction coefficient at 355 and 532 nm and particle linear depolarization at 355 and 532 nm (Maestri et al, 2010;Griaznov et al, 2007;Di Girolamo et al, 1996, 2009b.…”
Section: Lidar and Radar Systemsmentioning
confidence: 99%
“…In Europe, the Convective and Orographically induced Precipitation Study (COPS) was conducted from July to August 2007 around the Black Forest, which is a broad region around southern Germany and eastern France including mountainous areas. One of the results of this study suggests that the interaction of the thermally induced local circulation and the mesoscale convergence zone is an important trigger for the formation of strong updraft that can intrude into the stable layer with a small convective available potential energy (CAPE) condition (Kalthoff et al 2009;Barthlott et al 2010;Bennett et al 2011). In the United States, the Cumulus, Photogrammetric, In situ, and Doppler Observation Experiment (CUPIDO) investigated convection from a very early stage using stereo photogrammetric analysis, soundings, and airborne sensor observation around the Santa Catalina Mountains, Arizona (Zhender et al 2007).…”
Section: Introductionmentioning
confidence: 97%
“…Using the WRF model for simulation of a convection situation over the Black Forest mountains in southwest Germany, Bennett et al (2011) found that a high resolution of 700 m was needed to capture the fine-scale motions over the complex terrain for convection to be reproduced at the correct location and with about the right intensity to match the observations. A positive impact of increased model resolution was also found by Colle and Mass (2000) for the Cascade Mountains in the Pacific Northwest of the USA when moving from a grid spacing of 36 to 12 to 4 km.…”
Section: Introductionmentioning
confidence: 99%